Sistem PENGEMBANGAN SISTEM INFORMASI DOSEN WALI UNTUK OPTIMALISASI BIMBINGAN AKADEMIK: PENGEMBANGAN SISTEM INFORMASI DOSEN WALI UNTUK OPTIMALISASI BIMBINGAN AKADEMIK - Saifu Rohman; Dhea Anggrestyn; Akhmad Khadziq Khafifi (Tekompedia : Jurnal Ilmiah Ilmu Komputer, 2026)
Academic advising is an important activity between academic advisors and students to ensure that study plans run in accordance with applicable regulations. In many study programs, this process is still carried out manually, so consultation data is often not well recorded and communication becomes less effective. This condition encourages the development of an Academic Advisor Information System that can help manage the advising process in a structured manner. The system is designed to provide features for submitting consultation requests, reviewing study plans (KRS), recording the results of advising sessions, as well as displaying student information for academic advisors. The development stages are carried out starting from needs analysis, interface design, development of main functions, to simple testing to ensure the system runs according to its initial objectives. Based on the results of initial use, this system is considered capable of